Perspectives of parents on the meaning of happiness in children with long‐term illness: A hybrid concept analysis - Ruth Nimota Nukpezah; Mohammad Ali Cheraghi; Shahzad Pashaeypoor; Akram Sadat Sadat Hoseini (Wiley, 2020)
Abstract Aim To define the concept of happiness among children with chronic disease. Background Happiness is an old human quest, the existing literature on the definition of happiness among children with chronic diseases is sparse. Methods The three‐phase hybrid model was used. In the first (theoretical) phase, a literature review was conducted. In the second (fieldwork) phase, the semi‐structured interview data were analysed through content analysis. Ten participants were purposively sampled. In the third (final analytic) phase, the practical definition of the concept was identified. Results The practical definition of happiness in a Ghanaian chronically ill child is the "subjective and positive lifelong process of adapting to biological, physiological, psychosocial, economic and environmental changes caused by the disease trajectory, which affects the well‐being of the child and the family." Conclusions This study offers a background for selecting appropriate health indicators and outcome measures in promoting happiness in children with chronic diseases.